A narrative literature review examining cancer treatment issues for patients living with intellectual disabilities. (October 2018) - Witham, Gary; Haigh, Carol
Abstract: Purpose: The experiences of cancer care can be mediated by many different factors and this narrative literature review aims to explore the experiences of cancer care in relation to people with intellectual disabilities receiving cancer treatment. Method: We undertook a search for articles in English from (Jan) 2000–(Feb) 2018 using Medline, CINAHL, ScienceDirect, ASSIA and Wiley. The inclusion criteria are 2000–2018, English language and focussing on experiences of cancer journey. We used a narrative approach and thematically analysed the data. Results: There were 10 papers that met our inclusion/exclusion criteria. The themes generated included communication issues, information giving and decision-making. The literature suggests that communication and decision-making within cancer care are often mediated through support workers or family carers with minimal involvement of the person with intellectual disabilities. Information-giving by health professionals and support workers to people with intellectual disabilities was limited. This was often justified by the perceived distress this may cause. Conclusion: Training for health professionals and support workers in supporting people with intellectual difficulties is required for more effective communication in cancer care. Highlights: Health professionals need to explore the problems of navigating cancer treatment for people with intellectual disabilities. Adequate time and planning needs to be designated to consultations involving decision-making. Oncology nurses need training in supporting patients with intellectual disabilities.